Metamorphism and deformation on subduction interfaces: 1. Physical framework - England, PC; Smye, AJ (American Geophysical Union, 2023)
Abstract A thermal and mechanical framework is presented for analysis of pressure-temperature (P-T) data and structural observations from high-pressure-low-temperature (HPLT) terrains. P-T data from 281 HPLT rocks exhibit two regimes separated at a pressure of ∼1.5 GPa, which corresponds to the modal maximum depth of thrust faulting in subduction zones. At pressures ≲1.5 GPa, interpreted as recording conditions on the plate interface, temperatures increase at about 350°C/GPa and are consistent with conditions calculated for shear stresses of ∼30–100 MPa on the interface. Such shear stresses are high enough to carry several kilometers' thickness of sediment at least to the base of the plate interface. Burial of material on plate interfaces occurs predominantly during large-to-great earthquakes; the exhumation phase involves contrasts in ascent rates of adjacent units, because of their differing buoyancies and strengths. In consequence, juxtaposition of unrelated rock types is expected to be ubiquitous, during both descent and ascent. The scarcity of temperatures higher than ∼650°C at pressures ≳1.5 GPa may reflect loss of material from the wedge-slab interface by buoyant ascent. Exhumation of rocks in the subduction interface requires substantial reduction in shear stress, most plausibly by (near-)cessation of subduction. During prograde metamorphism temperatures increase smoothly with depth in the plate interface, with almost isothermal compression in the wedge-slab interface. Following cessation of subduction, rocks rising along the wedge-slab interface are likely to heat slightly during decompression. Within the plate interface, temperatures drop following the cessation of shear heating, and rocks follow counter-clockwise hairpin PT paths.